2015
DOI: 10.1088/0957-4484/26/5/055102
|View full text |Cite
|
Sign up to set email alerts
|

Chlorin e6–ZnSe/ZnS quantum dots based system as reagent for photodynamic therapy

Abstract: Stable water-soluble complexes of Cd-free ZnSe/ZnS quantum dots (QDs) and chlorin e6 complexes have been prepared. These complexes have shown approximately 50% intracomplex fluorescence resonance energy transfer from QDs to chlorin e6. The photodynamic therapy (PDT) test of the complexes against the Erlich acsite carcinoma cell culture demonstrated a two-fold enhancement of the cancer cell photodynamic destruction as compared to that of free chlorin e6 molecules. It was shown that the PDT effect was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 49 publications
(52 reference statements)
0
38
0
1
Order By: Relevance
“…Several examples of Cd-based QDs conjugated with PSs have been reported in literature [156][157][158] and used for cancer PDT in vitro, but the main disadvantage of such nanosystems is related to the elevated metal-induced cytotoxicity, limiting in vivo applications. As an alternative, ZnSe/ZnS quantum dots complexed with the PS Ce6 were synthetized as stable and water-soluble nanosystems [159]. The authors reported a very efficient QD to Ce6 intracomplex photoexcitation energy transfer (almost 50% FRET efficiency) that significantly improved PDT efficacy in EAC carcinoma cells in vitro due to synergistic effects of FRET mediated PDT and improved cellular uptake of Ce6 delivered by QDs with respect to the PS delivered in the free form.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%
“…Several examples of Cd-based QDs conjugated with PSs have been reported in literature [156][157][158] and used for cancer PDT in vitro, but the main disadvantage of such nanosystems is related to the elevated metal-induced cytotoxicity, limiting in vivo applications. As an alternative, ZnSe/ZnS quantum dots complexed with the PS Ce6 were synthetized as stable and water-soluble nanosystems [159]. The authors reported a very efficient QD to Ce6 intracomplex photoexcitation energy transfer (almost 50% FRET efficiency) that significantly improved PDT efficacy in EAC carcinoma cells in vitro due to synergistic effects of FRET mediated PDT and improved cellular uptake of Ce6 delivered by QDs with respect to the PS delivered in the free form.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%
“…As well, Föster Resonance Energy Transfer (FRET) has been proposed for the activation of PS to enhance the production of ROS [165,166]. Martynenko et al employed ZnSe/ZnS QDs as energy donors for chlorin-Ce6 PS molecules [167]. In vitro experiments revealed that the conjugation of the PS molecules with the QDs resulted in a twofold enhancement in the killing of the cancer cell in comparison to the free Ce6 molecules.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Due to the efficient photoexcitation energy transfer (ET), singlet oxygen generation of tetrapyrrole compound can be enhanced. Accordingly, photodynamic effect of QD/tetrapyrrole system can be significantly higher compared to that of free tetrapyrrole [7].…”
Section: Introductionmentioning
confidence: 97%